The important role of retrofitting in agricultural machinery: a case study for techniques and applications - Pişkin, В.; Sağlam, R. (Геотехнічна механіка, 2017)
The article provides a comparative analysis of important role of retrofitting in agricultural machinery. Over the last fifteen years, many new technologies have been developed for, or adapted to, agricultural use. Examples of these include: low-cost positioning systems, such as the Global Positioning System, proximal biomass and Leaf Area Index (LAI) sensors mounted on-board agricultural machinery, geophysical sensors to measure soil properties and low-cost, reliable devices to store and exchange/share the information. Combined, these new technologies produce a large amount of affordable high resolution information and have lead to the development of fine-scale or site-specific agricultural management that is often termed Precision Agriculture. Farming moves into the 21st century with tractors carrying satellite navigation receivers, radar guns, and computers. socioagricultural systems and, as a consequence, adopters are currently becoming more and more complex in current economies and it might prove difficult to analyse patterns and forecast trends. The conclusions of this study are of course tentative. Hence, there is need for much more detailed research and analysis concerning the attitudes of adopters of innovations in agricultural tractors, in particular in the presence of fast-changing scenarios due to a more and more acceleration of technological change.